Direct Ink Writing of 4D Structural Colors. (6th May 2022) - Sol, Jeroen A. H. P.; Smits, Luc G.; Schenning, Albert P. H. J.; Debije, Michael G.
Abstract: Additive manufacturing with stimuli‐responsive materials—4D printing—is a rapidly growing field, with direct ink writing allowing deposition of a wide variety of materials. The synthesis of a humidity‐sensitive cholesteric liquid crystal oligomer ink is reported. With the responsive cholesteric ink, demonstrator devices exhibiting the ink's "four dimensionality" are printed in disparate fashions: as a structural color change or as a preprogrammed deformation mode. After printing, the photonic ink changes color in response to atmospheric humidity, demonstrated as a hydrochromic coating precisely deposited atop a 3D‐printed beetle. After activation in aqueous acid, the beetle exhibits vibrant color shifts across the visible spectrum. Alternatively, a scallop‐inspired actuator with a 3D‐programmed structural color is selectively treated with acid, to allow reversible "opening" and "closing" when exposed to humid and dry air, respectively. The ink enables additive manufacturing of both monolithic and multimaterial stimuli‐responsive, shape‐changing, structurally colored objects, toward broad application of cholesterics in future "smart, " 4D structurally colored devices. Abstract : Inspired by natural examples of hydrochromicity, an ink is developed to "4D print" objects with environmentally responsive structural colors. The devices designed using this ink exploit their reversible response to water in two distinct manners: as color or shape changes.